Pengembangan Business Model Canvas Inkubator Bisnis Putra Sang Fajar Dengan Pendekatan Porter 5 Forces Analysis - Utama, Adiguna; Wardani, Shanti Ike; Kurniawan, Hindra (Benefit: Jurnal Manajemen dan Bisnis, 2024)
Business incubation is a powerful tool for stimulating economic growth and entrepreneurship. However, to be sustainable, a business incubator needs to formulate the right strategy and business model. Several management tools that can be used to formulate strategies and business models include the Business Model Canvas and Porter 5 Forces Analysis. This study aims to develop a Business Model Canvas for business incubators using the Porter 5 Forces Analysis approach. The research method employed is qualitative-descriptive research, gathering primary data through questionnaires from 34 respondents and secondary data from literature studies. The primary data were analyzed using SEM-PLS. The results indicate that the Porter 5 Forces Analysis approach can elucidate the Business Model Canvas. The study concludes that business incubators can utilize the Business Model Canvas as an operational guide, though further research is necessary to formulate future strategies